Analysis of PT Pertamina’s 2020-2024 Financial Ratios: Liquidity, Solvency, Activity, and Profitability - Azzahra, Syakirah; Hutagalung, Gerifour; Rizka, Sofa Aulia; Sembiring, Dealova Velonika Br; Sembiring, Anggi Herawati Br; Purba, Gracia Br; Putri, Nasywa; Nasution, Anggi Pratama (EDUCTUM: Journal Research, 2025)
This study examines PT Pertamina (Persero)’s financial performance from 2020 to 2024 using liquidity, solvency, profitability, and activity ratios. Data were sourced from the company’s annual financial reports over the five-year period. The findings reveal fluctuating liquidity, particularly in 2020 due to the pandemic, followed by improvement through 2024. Solvency analysis shows a high leverage level, reflecting project funding and government mandates, but still within reasonable bounds. Profitability dropped sharply in 2020, rebounded in 2021–2022 with rising oil prices, and declined again in 2023–2024 because of subsidy and operational cost pressures. Activity ratios demonstrate a steady increase in asset management efficiency. Overall, despite external challenges and shifting policy requirements, Pertamina has maintained its financial stability and operational resilience throughout the review period.